RELATIONSHIP BETWEEN COMPENSATION, MOTIVATION AND WORK DISCIPLINE TOWARDS EMPLOYEE PERFORMANCE AT RSD DR. SOEBANDI JEMBER DISTRICT - Tua S, Marolop Bungaran; Dwi Cahyono; Diah Probowulan (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research was conducted at dr Soebandi Regional Hospital. This study consists of two variables, namely the independent variable (free), which consists of compensation (X1), work discipline (X2), and work motivation (X3), while the dependent variable (bound) is Employee Performance (y). This study aims to determine whether there is a significant influence between compensation, work discipline, and work motivation on employee performance with a sample of 162 respondents. Method: The data collection methods used in this study include interviews, observations, questionnaires, and literature studies. The data analysis technique in this study employs multiple linear analysis with data processing using Statistical Product and Service Solutions (SPSS) software 20. The data analysis methods include validity test, reliability test, multicollinearity test, heteroscedasticity test, partial t-test, F-test (simultaneous test), and coefficient of determination (R2). Results: The results of this study indicate that the variables of compensation, work discipline, and work motivation have a simultaneous influence on employee performance. Partially, the compensation and work motivation variables show an influence. Based on the results of the analysis of the coefficient of determination, the R-square value is 0.810 or 81%. Novelty: This study provides empirical evidence of the influence of compensation and work motivation on employee performance in a hospital setting, emphasizing the importance of these factors in workforce management.